Analisis Kepuasan Konsumen Terhadap Kue Baytat Bengkulu - Eka Kurniati; Evanila Silvia; Zulman Efendi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2016)
The aim of research was to identify the attributes that baytat consumers want, determine the customer satisfaction of baytat cake and get a map attributes of baytat cake. Locations were selected intentionally (purposive). Variables and attributes used are: 1) quality of product (color of cake, aroma of cake, texture of cake, taste of cake, and the shelf life of product), 2) packaging products (appeal illustration, color packaging, capabilities of packaging to protect the product, practicality packaging) and 3)  price of product. Identify the attributes that consumers want analyzed by validity and reliability test; used 22 respondents. Level of customer satisfaction was analyzed by CSI (Customer Satisfaction Index) and map attributes were analyzed using Importance Performance Analysis (IPA); total respondents are 100 consumers with convenience sampling technique. The results showed that the attributes that consumers want baytat is an attraction illustration, color packaging, packaging capabilities protect products, practical packaging, the color of the cake, cake aroma, the texture of the cake, cake flavor, shelf life of products and product prices. CSI analysis results indicate the level of customer satisfaction with cake baytat of 80.41%. Map quadrant of the following attributes: quadrant 1 (the color of the cake and the price of the product), Quadrant II (cake flavor, aroma of cookies and texture of the cake), Quadrant III (packaging capabilities, appeal of the packaging and packaging color) and Quadrant IV (the shelf life of product and practicality packaging).